Louis Pasteur : de la physico-chimie à la biologie - This, Hervé (Comptes Rendus. Chimie)
Louis Pasteur began his scientific research with crystallographic studies, which led him to distinguish different forms of tartaric acids and tartarates. His appointment to the University of Lille, in an industrial environment that led him to study amyl alcohols, helped to reorient his scientific activity, but he remained mainly driven by his hypothesis that “molecular dissymmetry” was the prerogative of the living. Stumbling on the optical inactivity of certain organic compounds, he progressively abandoned a research for which chemical concepts were missing and which were only elaborated later, by others, to study fermentation, before going to explore the micro-organisms which caused them.